PERAN PEMANFAATAN AI DAN TIKTOK TERHADAP KINERJA BISNIS UMKM MELALUI PENGETAHUAN WIRAUSAHA DI TANGERANG - Matthew Denilson Martono; Apriani Simatupang (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) and TikTok utilization on MSME business performance, with entrepreneurial knowledge as a mediating variable. The study was conducted on micro and small business owners in Tangerang who have utilized AI and/or TikTok in their business activities. A quantitative approach with a cross-sectional design was employed. Data were collected through an online survey of 467 respondents selected using purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that the utilization of AI and TikTok has a positive and significant effect on entrepreneurial knowledge. In addition, entrepreneurial knowledge was also found to have a positive effect on business performance. The findings further indicate that AI and TikTok not only have a direct effect on business performance, but also an indirect effect through entrepreneurial knowledge as a mediator. These results confirm that the use of digital technology, accompanied by improved entrepreneurial knowledge, can become an important strategy to strengthen the competitiveness, efficiency, and sustainability of MSMEs. This study provides practical implications for business owners and policymakers in promoting a more targeted and effective digital transformation of MSMEs